The Minangkabau Woman Against Discrimination: Rahmah El Yunusiyyah's Islamic Education Thoughts (1900-1969) - Setiawan, Agus Mahfudin; Hidayati, Nurul; Hasanah, Uswatun; Khairunnisa, Briliant Windy (Faculty of Ushuluddin, Adab, and Da'wah, State Islamic University of Palangkaraya, 2024)
This article aims to explore Rahmah El Yunusiyyah's resistance against discrimination faced by Minangkabau women in accessing education. The study in this article is conducted through historical methodology with a biographical and literature approach. The primary data source in this study is the manuscript Boekoe peringatan 15 tahoen Dinijjah School Poeteri Padang Pandjang. The data obtained was analysed using the historical analysis model. According to the analysis of the data obtained, it was found that Rahmah El Yunusiyyah's resistance and struggle against discrimination faced by Minangkabau women was motivated by the socio-cultural reality of Minangkabau society at that time. Minangkabau customs and traditions at that time considered women's lives to be under the power of men so that they did not need education. This study also found that Rahmah El Yunusiyyah's Islamic education thoughts were not only campaigned in the public sphere, but also realised by establishing special educational institutions for women based on Islamic principles. These ideas are women as Madrasatul Ula, Tertib-Sopan, and the integration of traditional Minangkabau values with